Students’ High Achievement on Learning Style Preferences in Chinese Department, Binus University - Yetty Go (Lingua Cultura, 2013)
Every student certainly demonstrates different achievement in her/his Chinese language learning process because every student has her/his own individual way to resolve their problems in learning. In learning process, student’s individual differences exist. These differences lead to different learning speed and learning style of the student. The purpose of this study was to investigate the high achievement students’ learning styles. This study was based on Reid’s learning styles theory and also uses Reid’s Perceptual Learning Style Preference Questionnaire (PLSPQ) to investigate student’s learning styles. The main finding of this study is that student’s learning style preference is group style. According to student learning style preferences results, students prefer to learn together with others or in group and learn in a more interactive way.